1963
DOI: 10.1128/jb.85.2.329-338.1963
|View full text |Cite
|
Sign up to set email alerts
|

BIOSYNTHESIS OF GRAMICIDIN AND TYROCIDINE IN THE DUBOS STRAIN OF BACILLUS BREVIS I

Abstract: Biosynthesis of gramicidin and tyrocidine in the Dubos strain of Bacillus brevis. I. Experiments with growing cultures. J. Bacteriol. 85:329-338. 1963.-A simple chromatographic method was developed for the isolation of gramicidin and tyrocidine from tyrothricin of Bacillus brevis. A Tryptone-yeast extract-glucose medium containing mineral salts gave the best yields of peptides in a stationary culture of the organism. The incorporation of suitable C'4-labeled amino acids into gramicidin and tyrocidine was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…In vivo (102,112,130,168) as well as in vitro (30,33,34,37,58,63,93,97,120,128,153) experiments have revealed that structurally similar amino acids and amino acid analogues can replace certain of the amino acid residues of the peptide chain during antibiotic synthesis. These studies have demonstrated that antibiotic formation is catalyzed by enzymes with rather broad specificities.…”
Section: Specificity Of Incorporationmentioning
confidence: 99%
“…In vivo (102,112,130,168) as well as in vitro (30,33,34,37,58,63,93,97,120,128,153) experiments have revealed that structurally similar amino acids and amino acid analogues can replace certain of the amino acid residues of the peptide chain during antibiotic synthesis. These studies have demonstrated that antibiotic formation is catalyzed by enzymes with rather broad specificities.…”
Section: Specificity Of Incorporationmentioning
confidence: 99%
“…The tyrothricin producer bacterial strain was initially referred to as the Dubos strain of Bacillus brevis (Okuda et al ), and renamed to Bacillus aneurinolyticus (Shida et al ). These authors subsequently suggested further reclassification of the strain to Br.…”
Section: Methodsmentioning
confidence: 99%
“…(Uemura et al, 1963) or butan-l-ol-acetic acid-water (12:3:5, by vol.). Papers were air-dried, and gramicidin and tyrocidine were detected either by dipping the paper in 7M-HN03 (Okuda et al, 1963), when yellow spots appeared on a white background (detection limits 5S,g of tyrocidine and 3,ug of gramicidin), or by dipping the paper in or spraying it with 0.2 % (w/v) ninhydrin in dry acetone and heating it at 60°C for 30min; tyrocidine gave a blue-grey spot and gramicidin a grey spot (detection limit about 100,ug in each case).…”
Section: Methods For Separating and Detecting Ethanol-soluble Peptidesmentioning
confidence: 99%